Acute Low Back Pain: Differential Somatosensory Function and Gene Expression Compared With Healthy No-Pain Controls. Issue 11 (November 2016) - Starkweather, Angela R.; Ramesh, Divya; Lyon, Debra E.; Siangphoe, Umaporn; Deng, Xioayan; Sturgill, Jamie; Heineman, Amy; Elswick, R.K.; Dorsey, Susan G.; Greenspan, Joel
Abstract : Objectives: Low back pain (LBP) is the second most frequently diagnosed pain condition in the United States, and although a majority of individuals have resolution of pain during the acute period, an estimated 40% of individuals will experience persistent pain. Given the heterogenous nature of LBP, this study sought to describe and compare somatosensory and molecular (gene expression) profiles between individuals with acute LBP and healthy no-pain controls. Methods: Using a previously established protocol, we comprehensively assessed somatosensory parameters among 31 no-pain control participants and 31 participants with acute LBP. Samples of whole blood were drawn to examine mRNA expression of candidate genes involved in the transduction, maintenance, and modulation of pain. Results: The acute LBP group exhibited increased pain sensitivity to cold stimuli, mechanical stimuli, including mechanical temporal summation at both the painful back area and remote location suggesting a mechanism of enhanced central nervous system excitability. In addition, deep tissue-specific peripheral sensitization was suggested due to significant differences in pressure pain threshold of the painful back area, but not the remote body site. Several genes that were differentially expressed were significantly associated with somatosensory alterations identified in the acute LBP group. Discussion: Acute LBP participants showed selective pain sensitivity enhancement and differential gene expression profiles compared with pain-free controls. Further research to characterize pain-associated somatosensory changes in the context of altered mRNA expression levels may provide insight on the molecular underpinnings of maladaptive chronic pain.